Identification and characterization of circular RNAs in Qinchuan cattle testis. Issue 7 (25th July 2018) - Gao, Yuan; Wu, Mingli; Fan, Yingzhi; Li, Shipeng; Lai, Zhenyu; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong; Dang, Ruihua
Abstract : Circular RNA (circRNA) is a new class of non-coding RNA that has recently attracted researchers' interest. Studies have demonstrated that circRNA can function as microRNA sponges or competing endogenous RNAs. Although circRNA has been explored in some species and tissues, the genetic basis of testis development and spermatogenesis in cattle remains unknown. We performed ribo-depleted total RNA-Seq to detect circRNA expression profiles of neonatal (one week old) and adult (4 years old) Qinchuan cattle testes. We obtained 91 112 596 and 80 485 868 clean reads and detected 21 753 circRNAs. A total of 4248 circRNAs were significantly differentially expressed between neonatal and adult cattle testes. Among these circRNAs, 2225 were upregulated, and 2023 were downregulated in adult cattle testis. Genomic feature, length distribution and other characteristics of the circRNAs in cattle testis were studied. Moreover, Gene Ontology and KEGG pathway analyses were performed for source genes of circRNAs. These source genes were mainly involved in tight junction, adherens junction, TGFβ signalling pathway and reproduction, such as PIWIL1, DPY19L2, SLC26A8, IFT81, SMC1B, IQCG and TTLL5 . CircRNA expression patterns were validated by RT-qPCR. Our discoveries provide a solid foundation for the identification and characterization of key circRNAs involved in testis development or spermatogenesis.